Flying J : governance through crash and takeoff - Shein, James B., 1942- (SAGE knowledge. Cases., 2016)
Flying J was a family-owned company that operated travel plazas, oil refineries, a bank for trucking companies and other related businesses. In early 2009, Crystal Call Maggelet, the majority shareholder and new CEO of Flying J, was tasked with saving the company founded by her father in 1968. This case explains how she set about salvaging the organisation, which had grown from four gas stations to become a vertically integrated $18 billion company.